Can "Oil Space" and "Oil in Space" Be United?. Issue 10 (23rd February 2021) - Shafranik, Iu.K.; Kriukov, V.A.
ABSTRACT: The development of Russia's oil and gas sector has its own essential features, due not only to the characteristics of its resource base but also to the significant influence of the spatial factor. Small and medium-sized companies oriented toward high tech and a priori innovation have more favorable prospects in previously developed areas, while access to new areas is more consistent with the operations and development of the leading large, vertically integrated companies.